Dose rate and dose robustness for proton transmission FLASH-RT treatment in lung cancer - Wei, Shouyi; Lin, Haibo; Huang, Sheng; Shi, Chengyu; Xiong, Weijun; Zhai, Huifang; Hu, Lei; Yu, Gang; Press, Robert H.; Hasan, Shaakir; Chhabra, Arpit M.; Choi, J. Isabelle; et al. (Frontiers in Oncology, 2022)
Purposes To evaluate the plan quality and robustness of both dose and dose rate of proton pencil beam scanning (PBS) transmission FLASH delivery in lung cancer treatment. Methods and materials An in-house FLASH planning platform was used to optimize 10 lung cancer patients previously consecutively treated with proton stereotactic body radiation therapy (SBRT) to receive 3 and 5 transmission beams (Trx-3fds and Trx-5fds, respectively) to 34 Gy in a single fraction. Perturbation scenarios (n=12) for setup and range uncertainties (5 mm and 3.5%) were introduced, and dose-volume histogram and dose-rate-volume histogram bands were generated. Conventional proton SBRT clinical plans were used as a reference. RTOG 0915 dose metrics and 40 Gy/s dose rate coverage (V40Gy/s) were used to assess the dose and dose rate robustness. Results Trx-5fds yields a comparable iCTV D2% of 105.3%, whereas Trx-3fds resulted in inferior D2% of 111.9% to the clinical SBRT plans with D2% of 105.6% (p<0.05). Both Trx-5fds and Trx-3fds plans had slightly worse dose metrics to organs at risk than SBRT plans. Trx-5fds achieved superior dosimetry robustness for iCTV, esophagus, and spinal cord doses than both Trx-3fds and conventional SBRT plans. There was no significant difference in dose rate robustness for V40Gy/s coverage between Trx-3fds and Trx-5fds. Dose rate distribution has similar distributions to the dose when perturbation exists. Conclusion Transmission plans yield overall modestly inferior plan quality compared to the conventional proton SBRT plans but provide improved robustness and the potential for a toxicity-sparing FLASH effect. By using more beams (5- versus 3-field), both dose and dose rate robustness for transmission plans can be achieved.